Inducible gene expression: diverse regulatory mechanisms - Weake, Vikki M.; Workman, Jerry L. (Nature reviews. Genetics, 2010)
Key Points Expression of target genes in response to extracellular stimuli is activated by means that include activation of RNA polymerase II (Pol II)-dependent transcription. Multiple processes during the early stages of Pol II-dependent transcription are subject to regulation and can therefore function as the rate-limiting step during activation of target genes. Activator-dependent recruitment of Pol II and the general transcription factors is essential for high levels of transcription at inducible genes. This process must occur at all induced genes before activation, whether or not recruitment of polymerase is rate-limiting with regards to activation. The kinetics of Pol II recruitment and transcription initiation can be stimulated by nucleosome-remodelling complexes that use the energy from ATP hydrolysis to move or displace histones from DNA. Co-activators are essential for activator-dependent recruitment of Pol II and the general transcription factors. Mediator and the histone acetyltransferase complex SAGA are well-characterized examples of co-activators. Transcription can be regulated at steps that occur after the recruitment of Pol II. These steps include the release of Pol II from a paused state close to the promoter into active transcription elongation in the coding region of the gene. The rate-limiting step of transcription can differ between various inducible genes. Signalling kinases such as MAPKs sometimes localize to the promoters of target genes at which they can function as transcriptional activators, rapidly facilitating the switch between activated and repressed states of gene expression. The rapid induction of specific sets of genes is required for cells to respond to external cues. Transcription of eukaryotic inducible genes is controlled at multiple steps, including activator recruitment and polymerase pausing, and is influenced by chromatin remodelling and signal transduction. The rapid activation of gene expression in response to stimuli occurs largely through the regulation of RNA polymerase II-dependent transcription. In this Review, we discuss events that occur during the transcription cycle in eukaryotes that are important for the rapid and specific activation of gene expression in response to external stimuli. In addition to regulated recruitment of the transcription machinery to the promoter, it has now been shown that control steps can include chromatin remodelling and the release of paused polymerase. Recent work suggests that some components of signal transduction cascades also play an integral part in activating transcription at target genes.